STUDI EFEKTIFITAS PENERAPAN UU NO. 19 TAHUN 2002 TENTANG HAK CIPTA - SEMAUN, SAHRIAH (P3M STAIN Parepare, 2014)
The purpose of this study was to determine how the application of copyright law to provide adequate legal protection for the recording industry and to determine the role of law enforcement offcials with regard to the effectiveness of the implementation of Law No. 19/2002 about the copyright of the record company Restu Music Record in the District Pinrang.The legal protection given to the rights of the creator or copyright holder in the implementation of the agreement on basing a song to the provisions contained in the Act No. 19 of 2002 on Copyright, in particular on Article 12 of the Copyright Act. Form of legal protection against record company Restu Music Record confrmed by providing criminal sanctions against those who violate copyright by unlawful means.Law enforcement offcials, in this case the police and prosecution had attempted to use the Act No. 19 of 2002 on Copyright. The role of the police can be seen from the implementation of the raids and the raids of establishments selling pirated goods, as well as the confscation of proceeds of crime of copyright infringement. While the role of prosecutors are trying to bring the perpetrators of copyright infringement to court to seek supporting evidence that copyright piracy